Optimized respiratory‐resolved motion‐compensated 3D Cartesian coronary MR angiography. Issue 6 (22nd April 2018) - Correia, Teresa; Ginami, Giulia; Cruz, Gastão; Neji, Radhouene; Rashid, Imran; Botnar, René M.; Prieto, Claudia
Abstract : Purpose: To develop a robust and efficient reconstruction framework that provides high‐quality motion‐compensated respiratory‐resolved images from free‐breathing 3D whole‐heart Cartesian coronary magnetic resonance angiography (CMRA) acquisitions. Methods: Recently, XD‐GRASP (eXtra‐Dimensional Golden‐angle RAdial Sparse Parallel MRI) was proposed to achieve 100% scan efficiency and provide respiratory‐resolved 3D radial CMRA images by exploiting sparsity in the respiratory dimension. Here, a reconstruction framework for Cartesian CMRA imaging is proposed, which provides respiratory‐resolved motion‐compensated images by incorporating 2D beat‐to‐beat translational motion information to increase sparsity in the respiratory dimension. The motion information is extracted from interleaved image navigators and is also used to compensate for 2D translational motion within each respiratory phase. The proposed Optimized Respiratory‐resolved Cartesian Coronary MR Angiography (XD‐ORCCA) method was tested on 10 healthy subjects and 2 patients with cardiovascular disease, and compared against XD‐GRASP. Results: The proposed XD‐ORCCA provides high‐quality respiratory‐resolved images, allowing clear visualization of the right and left coronary arteries, even for irregular breathing patterns. Compared with XD‐GRASP, the proposed method improves the visibility and sharpness of both coronaries. Significant differences ( p  < .05) in visible vessel length and proximal vessel sharpness were found between the 2 methods. The XD‐GRASP method provides good‐quality images in the absence of intraphase motion. However, motion blurring is observed in XD‐GRASP images for respiratory phases with larger motion amplitudes and subjects with irregular breathing patterns. Conclusion: A robust respiratory‐resolved motion‐compensated framework for Cartesian CMRA has been proposed and tested in healthy subjects and patients. The proposed XD‐ORCCA provides high‐quality images for all respiratory phases, independently of the regularity of the breathing pattern.